STRATEGIC SEALIFT VESSEL IMPORT’S EFFECT ON THE PHILIPPINES-INDONESIA MILITARY COOPERATION - M. Fuad Hasan Alfarizi; Hidayatullah, Nur Luthfi (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2022)
This research discusses the Philippines-Indonesia military cooperation which was influenced by the Philippines’ policy to upgrade its national defense equipment by importing Strategic Sealift Vessels from Indonesia. The authors argue that the Philippines’ decision to import Strategic Sealift Vessels from Indonesia has significant impact towards developing military cooperation between the two countries. This research used a descriptive qualitative method with documentation and literature studies data collection techniques. This research elaborates on the concepts of international trade and military cooperation to describe the correlation between the Philippines’ import policy and military cooperation between the Philippines and Indonesia. This study concludes that the Philippines-Indonesia military cooperation before the import of Strategic Sealift Vessel was only motivated by political and security motives aimed at protecting both countries’ territories from internal and external threats. Meanwhile, the Philippines-Indonesia military cooperation after the import of Strategic Sealift Vessels was motivated by political, security and economic motives as well. It was discovered that the Philippines held a tender for warships import, which was won by Indonesia with USD 90 million worth in 2014. Afterwards, both countries agreed on a logistics and defense industrial cooperation with commitment to improve the economy in 2016. Finally, both countries continued to extend their military cooperation by signing a contract on Strategic Sealift Vessels trade in addition to an agreement in the field of defense and security in 2021.